La producción de aceite de pingüino en Patagonia y Malvinas (1850-1880) - Sofia Clara Haller; Susana V. García (Nuevo mundo - Mundos Nuevos, 2022)
Penguins were one of the many marine animals that became a commercial object by being connected to the great market and consumption of oils and skins of the 19th century. This article examines the production of oil obtained from these birds on the Patagonian and Falkland Islands coastline between the 1850s and 1880s, a peak period for this product and its exploitation in the region. Based on the analysis of different historical sources, some actors, business ventures, technical operations, and shipping connections involved in this hunting activities in three areas of the region are identified: the Tova and Leones islands on the Patagonian coast; the island of the States and the Malvinas archipelago. The case of this industry allows us to delve into the operation of extractive mechanics in the southwestern Atlantic coastline and shows how the trade in animal products generated territorial occupations, commercial connections and navigation routes of global commerce that integrated remote islands and desolate bays in their circuits.